“Putting on My Best Normal”: Social Camouflaging in Adults with Autism Spectrum Conditions - Hull, Laura; Petrides, K. V.; Allison, Carrie; Smith, Paula; Baron-Cohen, Simon; Lai, Meng-Chuan; Mandy, William (Journal of autism and developmental disorders, 2017)
Camouflaging of autistic characteristics in social situations is hypothesised as a common social coping strategy for adults with autism spectrum conditions (ASC). Camouflaging may impact diagnosis, quality of life, and long-term outcomes, but little is known about it. This qualitative study examined camouflaging experiences in 92 adults with ASC, with questions focusing on the nature, motivations, and consequences of camouflaging. Thematic analysis was used to identify key elements of camouflaging, which informed development of a three-stage model of the camouflaging process. First, motivations for camouflaging included fitting in and increasing connections with others. Second, camouflaging itself comprised a combination of masking and compensation techniques. Third, short- and long-term consequences of camouflaging included exhaustion, challenging stereotypes, and threats to self-perception.